Quadruple-responsive nanoparticle-mediated targeted combination chemotherapy for metastatic breast cancer. Issue 11 (11th March 2021) - Huang, Yamei; Xie, Dengchao; Gou, Shuangquan; Canup, Brandon S. B.; Zhang, Guizheng; Dai, Fangyin; Li, Changming; Xiao, Bo
Abstract : Multi-responsive nanoparticles loaded with curcumin and 5-fluorouracil showed synergistic treatment effects against metastatic breast cancer. Abstract : The synergism of combination chemotherapy can only be achieved under specific drug ratios. Herein, hyaluronic acid (HA)-functionalized regenerated silk fibroin-based nanoparticles (NPs) were used to concurrently deliver curcumin (CUR) and 5-fluorouracil (5-FU) at various weight ratios (3.3 : 1, 1.6 : 1, 1.1 : 1, 1 : 1, and 1 : 1.2) to breast tumor cells. The generated HA-CUR/5-FU-NPs were found to have desirable particle sizes (around 200 nm), narrow size distributions, and negative zeta potentials (about −26.0 mV). Interestingly, these NPs showed accelerated drug release rates when they were exposed to buffers that mimicked the multi-hallmarks in the tumor microenvironment (pH/hydrogen peroxide/glutathione/hyaluronidase). The surface functionalization of NPs with HA endowed them with in vitro and in vivo breast tumor-targeting properties. Furthermore, we found that the co-loading of CUR and 5-FU in HA-functionalized NPs exhibited obvious synergistic anti-cancer, pro-apoptotic, and anti-migration effects, and the strongest synergism was found at the CUR/5-FU weight ratio of 1 : 1.2. Most importantly, mice experiments revealed that HA-CUR/5-FU-NPs (1 : 1.2) showed a superior anti-cancer activity against metastatic breast cancer compared to the single drug-loaded NPs and non-functionalized CUR/5-FU-NPs (1 : 1.2). Collectively, these results demonstrate that HA-CUR/5-FU-NPs (1 : 1.2) can be exploited as a robust nanococktail for the treatment of breast cancer and its lung metastasis.